Regeneration of Pain, Touch, Cold, and Warmth, sensations in split thickness human skin grafts in adults (A clinical study) - Hatef., Mohammed B.; Kamal, Ahmed, M.; Sahan, Abbas M. (AL-Kindy College Medical Journal, 2013)
Back ground: Skin grafting is the most common formof reconstructive surgery, and regeneration ofsensations in skin grafts is a complex processinfluenced by many factors such as , the thickness ofthe graft, the depth of the grafted bed, meshing of thegraft, the condition of the bed and the surroundingarea. So many studies performed on this subject, someof them clinically based on subjective type of sensationtests, and others histological to detect the presence ofnerve fibers in the grafted skinObjectives: To detect return of sensations to splitthickness skin grafts by clinical methods.Methods: From Oct. 1995 to Oct. 2010, a clinicalprospective study performed in Al wasity Hospital forreconstructive surgery, Hilla teaching GeneralHospital, and Al kindy teaching General Hospital onrecovery of sensations in human split thickness skingrafts on 200 patients, 400 grafts. There were 120male, 80 female patients, there ages ranged from20 -61years with mean of 28 years. The regeneration ofsensation of pain, touch, cold, and warmth, was studiedwith the usual clinical methods. We studied; differentgraft thicknesses, depth of graft beds, meshing of thegrafts, grafts on early and late wound excisionsResults: in our study the regeneration of sensationsoccurred in the following order; pain, touch, cold ,warmth, and has been found to extend over a period of16days to 3 months, and sensations improve with timebut never recover completely even after several years.Conclusion: The recovery of sensation of grafted skinis a complex process that is influenced by manyfactors; some of them are related to the graft, to therecipient bed, to the patient as a whole, and occurs ifthe graft is applied on a sufficiently innervated bed.